2006
DOI: 10.1159/000097596
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Study on the Japanese Version of the Clinician’s Interview-Based Impression of Change

Abstract: Background/Aims: The Japanese version of the Clinician’s Interview-Based Impression of Change plus Caregiver Input (CIBIC-plus J) consists of 3 subscales: Disability Assessment of Dementia Scale (DAD), Behavioral Pathology in Alzheimer’s Disease Rating Scale (Behave-AD), and Mental Function Impairment Scale (MENFIS), as well as the Clinician’s Global Impression of Change (CGIC). While the interrater reliability of CGIC has already been reported, that of the 3 subscales has not. The aim of the present report wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…The CIBIC+, an alternate version of the CIBIC nonspecific to dementia including caregiver input, was used in 3 trials . The Japanese version of the CIBIC+ demonstrated high concurrent validity in AD with the DAD (r = 0.91) and the Mental Function Impairment scale (MENFIS; r = 0.99) . This study also showed low inter‐rater reliability (k = 0.45), but improved inter‐rater reliability when collapsed into a 3‐point scale (improved, no change, or worsened; k = 0.89) .…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The CIBIC+, an alternate version of the CIBIC nonspecific to dementia including caregiver input, was used in 3 trials . The Japanese version of the CIBIC+ demonstrated high concurrent validity in AD with the DAD (r = 0.91) and the Mental Function Impairment scale (MENFIS; r = 0.99) . This study also showed low inter‐rater reliability (k = 0.45), but improved inter‐rater reliability when collapsed into a 3‐point scale (improved, no change, or worsened; k = 0.89) .…”
Section: Resultsmentioning
confidence: 89%
“…The Disability Assessment for Dementia (DAD) scale was used in 4 trials and is a subscale of the Clinician's Interview Based Impression of Change scale (CIBIC) . In AD, the DAD shows high concurrent validity with the Rapid Disability Rating Scale‐2 (r = −0.85) and with the Japanese version of the Clinician Interview Based Impression of Change with caregiver input (CIBIC+) (r = 0.91) . The DAD demonstrates high test‐retest (r = 0.96) and inter‐rater reliability (k = 0.95) in AD, but has not been established for PDD .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, the concordance rate of the CIBIC-plus rating was relatively high when specialists conducted the rating based on videos of the interviews, indicating that the contents of the patient interviews are important [3,4]. We addressed the issue of how the use of the nursing-care services might affect the CIBIC-plus rating via interview of the caregivers.…”
Section: Discussionmentioning
confidence: 99%